Immune responses to hepatitis C virus (HCV): investigation of the role of L-ficolin and anti-E1E2 - Hamed, Mohamed R. (2009)
Hepatitis C virus (HCV) causes acute and chronic liver diseases in humans. Its two envelope proteins, E1 and E2, are heavily glycosylated. They interact with host cell receptors and provide a target for host immune recognition. The host virus interactions determine the pathogenesis and outcome of HCV infection. L-ficolin is a soluble pattern recognition molecule of importance in innate immune defence against microorganisms. It activates the lectin complement pathway upon binding to carbohydrate recognition patterns on microorganisms. It was hypothesised that L-ficolin could interact with HCV glycoproteins. Both recombinant and serum derived L-ficolin were investigated for binding to the envelope glycoprotein E1E2 of HCV. Specific, dose-dependent binding of L-ficolin to HCV glycoprotein E1E2 was observed. The interaction between L-ficolin and HCV particles in infected sera was also demonstrated. Binding of L-ficolin to HCV pseudoparticles expressing E1E2 glycoproteins resulted in neutralisation of virus infectivity. The serum L-ficolin level was significantly higher in patients with mild HCV liver fibrosis compared to patients with severe HCV liver fibrosis. These results suggest a potential protective effect of L-ficolin, as an innate immune defence, against HCV infection. To study the role of anti-HCV E1 and E2 (anti-E1E2) in HCV disease, the levels of anti-E1E2 antibodies were evaluated in 230 sera of patients with chronic hepatitis C by enzyme-linked immunosorbent assay. The antigens used were recombinant HCV glycoproteins derived from genotype 1 (H77c) and genotype 3 (UKN3A1.28). Seroreactivity was greater when sera were tested against antigen derived from their homologous genotype than against heterologous antigen. The seroreactivity was inversely proportional to the viral load and to the degree of liver ﬁbrosis. These results demonstrate that seroreactivity against E1E2 depends upon the genotypic origin of the E1E2 antigens and the infecting genotype, and suggest a possible protective effect of anti-E1E2 against disease progression.